2023
DOI: 10.1186/s12933-023-01738-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cardiometabolic drugs in reduction of epicardial adipose tissue: a systematic review and meta-analysis

Abstract: Background Epicardial adipose tissue (EAT) plays an important role in cardiometabolic risk. EAT is a modifiable risk factor and could be a potential therapeutic target for drugs that already show cardiovascular benefits. The aim of this study is to evaluate the effect of cardiometabolic drugs on EAT reduction. Methods A detailed search related to the effect on EAT reduction due to cardiometabolic drugs, such as glucagon-like peptide-1 receptor agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Subgroup analysis and sensitivity analysis were used to explore the heterogeneity. Publication bias was assessed by visually checking funnel plots and conducting Egger's regression and Begg's adjusted rank correlation asymmetry tests ( 22 24 ). P value < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Subgroup analysis and sensitivity analysis were used to explore the heterogeneity. Publication bias was assessed by visually checking funnel plots and conducting Egger's regression and Begg's adjusted rank correlation asymmetry tests ( 22 24 ). P value < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous classes of drugs have been used to target EAT amount; antidiabetic and lipid-lowering drugs are the most studied among them. 129,[140][141][142][167][168][169][170][171][172][173][174][175] 6.3.1 Sodium-glucose cotransporter-2 inhibitors Sodium-glucose cotransporter-2 (SGLT-2) inhibitors are a new type of antidiabetic drug that significantly reduce cardiovascular incidence and mortality in patients with T2DM. [176][177][178] Furthermore, existing evidence has shown that SGLT-2 inhibitors can significantly reduce body weight and VAT.…”
Section: Pharmaceutical Interventionsmentioning
confidence: 99%
“…In the past decade, four types of interventions have been proposed to reduce EAT volume, including exercise interventions, dietary interventions, bariatric surgery, and pharmaceutical interventions 129–134 (Figure 3). There have been a number of well‐designed tables summarizing related clinical studies in recent systematic reviews 134–142 …”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%
“…13 Indeed, GLP-1RA treatment, compared with SGLT2 inhibitors, led to a 2× stronger reduction in EAT thickness within 12 weeks. 14 Together, these may form the basis of GLP-1RAs' benefits in inflammatory HFpEF and pre-HF phenotypes. 4,5…”
Section: Potential Benefits Of Eat Glp-1r Modulation In Metabolic Inf...mentioning
confidence: 99%